Identification of QTL for seed dormancy from weedy rice and its application to elite rice cultivar ‘Ninggeng 4’ - 1 (My University, 2019)
Identification of QTL for seed dormancy from weedy rice and its application to elite rice cultivar ‘Ninggeng 4’
Keywords: QTL (Tính trạng số lượng); Lúa cỏ; Giống lúa Ninh Canh 4